Analisis Ekonomi Politik Terhadap Korupsi (Dalam Perspektif Struktural Menuju Pemahaman Teoritik Baru Tentang Korupsi Politik Di Indonesia) - Muhammad Ali (Universitas Muhammadiyah Mataram, 2018)
Corruption is an urgent issue that must be overcome, in order to achieve healthy economic growth. Various notes on corruption that are always preached by the mass media both print and electronic, illustrated the increase and development of corruption models. Anti-corruption rhetoric is not enough to resolve / dismiss this disgraceful practice. Legislation that is part of the legal politics made by the government, becomes meaning less, if not accompanied by seriousness to manifestation of existing legislation. Legal politics is not enough, if there is no recovery of the executor or the perpetrators of the law. This study aims to find out how the political economic implications of corruption in Indonesia, and what strategies can be done to minimize corruption practices and how multiplier effect for the efficiency and effectiveness of economic development in Indonesia. This research uses qualitative method with descriptive approach. In this case researchers describe the results of research. Therefore, researchers conducted observations and interviews then analyzed it with data collection, data reduction, data display, and conclusions. The results can be concluded that the eradication of corruption as if only a political commodity, powerful material rhetoric attract sympathy. Therefore, civil society's intelligence is needed to monitor and make political decisions to prevent the corruption of corruption in Indonesia. It is not easy to eliminate corruption but should be sought to minimize corruption.